Working to support research literacy and related skills among fully employed doctoral students: A course- based study - Wilkinson, Larrell L.; Bowman, Mary; Gontarz, Shelby; Hayes, Rashad; Hudson, Evan; Key, Johanna (Journal of Health and Physical Literacy, 2025)
The ability to design research studies and evaluations of interventions are competencies of a Certified Health Education Specialists (CHES) (NCHEC, 2022). Although a competency, doctoral students may be deficient in the performance of this area of responsibility. Research literacy is the cognitive and social understanding of the basic purpose, process, and value of research and research participation (Brody et al., 2013). Improving research literacy is important to both understand and conduct research and program evaluation. Thusly, the purpose of this study is to examine the influence of research course assignments in improving doctoral student research literacy and skills to perform research. Five (5) fully employed part-time doctoral students participated in the course evaluation. Students completed a pre/post course assessment. The students offered in-depth reflective descriptions of the course experience following specific assignments. The students then participated in a 1-hour focus group to reflect collectively on course assignments and their progress in research literacy and performance of research related skills. We expected to identify two main approaches of teaching health education/promotion research, one more content-centered and one more student-centered, would benefit students’ research literacy and skills. Student results from the baseline assessment demonstrated understanding of research and research practices, but little prior involvement in scholarly works. Students responded to inquiries related to learning strategies, appreciating student-centered approaches with tangible outcomes. While overall research literacy improved, students may still struggle with research concepts without continued reinforcement. Therefore, consistent efforts are needed to provide research training for students with full-time jobs in order to improve their motivation for applying these skills in practice.